2020
DOI: 10.1101/2020.02.13.942383
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dopaminergic modulation of human inter-temporal choice: a diffusion model analysis using the D2-receptor-antagonist haloperidol

Abstract: 14The neurotransmitter dopamine is implicated in diverse functions, including reward 15 processing, reinforcement learning and cognitive control. The tendency to discount future 16 rewards in value over time has long been discussed in the context of potential dopaminergic 17 modulation. Here we examined the effect of a single dose of the D2 receptor antagonist 18 Haloperidol (2mg) on temporal discounting. Our approach extends previous human 19 pharmacological studies in two ways. First, we applied state-of-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 68 publications
7
18
0
Order By: Relevance
“…In traditional value-based decisions assumed by the prospect theory, a decision-maker needs to integrate the value and probability of gain or loss to obtain an expected utility for each option (Tversky and Kahneman 1992). Together, our results here and previous studies (Wagner et al 2020) provide converging evidence that both reward value and probability can influence RT in equal choices. This raises the intriguing possibility of our results to be generalized to choices with the same expected utility but the different combinatory of value and probability.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In traditional value-based decisions assumed by the prospect theory, a decision-maker needs to integrate the value and probability of gain or loss to obtain an expected utility for each option (Tversky and Kahneman 1992). Together, our results here and previous studies (Wagner et al 2020) provide converging evidence that both reward value and probability can influence RT in equal choices. This raises the intriguing possibility of our results to be generalized to choices with the same expected utility but the different combinatory of value and probability.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, the accumulation rate is associated with the individual differences in working memory (Schmiedek et al 2007) and attention (Nunez et al 2017), while the non-decision time is faster in individuals with higher diffusion MRI-derived neurite density in the corticospinal tract, the primary motor output pathway (Karahan et al 2019). Recent research showed that both parameters can be influenced by reward magnitude (Wagner et al 2020), and the current study will examine further whether reward probability and preference influence the two model parameters.…”
Section: Introductionmentioning
confidence: 83%
“…First, leveraging the information contained in the full RT distributions can improve the stability of parameter estimates [37,38] . Second, by conceiving decision making as a dynamic diffusion process, a more detailed picture of the underlying latent processes emerges [39][40][41][42][43] . Recent studies, for instance, applied these techniques to temporal discounting, where they revealed novel insights into effects of pharmacological manipulation of the dopamine system on choice dynamics [42] .…”
Section: Introductionmentioning
confidence: 99%
“…Next, we incorporated response times (RTs) into the model by replacing the softmax choice rule with the drift diffusion model (DDM) [39][40][41][42] . The DDM models choices between two options as a noisy evidence accumulation that terminates as soon as the accumulated evidence exceeds one of two boundaries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation